GE_GERICHTE P/19286/2016 vom 26. Januar 2017 - GE Cour de justice (2017)
GESTION DÉLOYALE ; QUALITÉ POUR AGIR ET RECOURIR ; INTÉRÊT JURIDIQUEMENT PROTÉGÉ ; DOMMAGE DIRECT | CP.158; CPP.310; CPP.382; CPP.118; CPP.115